Policy Evaluation on Maritime Security Issues in Indonesia - Aria Cakra Wibawa; Bambang Supriyono; M. Khairul Muluk; Siti Rohmah (Wacana Journal of Social and Humanity Studies, 2020)
This paper aims to evaluate the implementation of the Maritime Security Policy in Indonesia. While the issues of maritime security vary, this paper focuses only on three issues in maritime security, which include maritime delimitation, Illegal Unreported, and Unregulated (IUU Fishing) and Piracy. It is argued that IUU Fishing as well as piracy and any other maritime security threats emerged due to unclear maritime delimitation. Indonesia is the biggest archipelagic state in the world neighboring by ten coastal states, which each of them needs clear maritime delimitation. While Indonesia has done much in fixing its maritime delimitation, yet much remains to be done. Furthermore, while a various international legal framework has been established relating to IUU Fishing, unfortunately, national laws concerning IUU Fishing still recall for never-ending debates. Similar to this, national laws in piracy are still out of date since such laws still regulated under Criminal Laws Code/ Kitab Undang-Undang Hukum Pidana (KUHP), which was adopted from Dutch laws many decades ago. Such conditions lead to insufficient policy implementation. This paper adopts a qualitative research method. Data collected from relevant informants and will be analyzed using policy implementation theory. It is submitted that in ensuring policy implementation, existing policies relating to maritime security, especially IUU Fishing as well as piracy needs to be revisited and revised to be in accordance with international policies and legal framework.